Storm rainfall analysis for upper Rajang River Catchment - Mohammad Ishamudin, Ismail (UNIMAS, 2006)
There are numerous examples throughout history where settlements, and even entire civilizations were damaged due to rampaging floods which were caused by heavy rains. Rainwater, in small amounts, are necessary as a water source, yet can cause flash floods and landslides in large amounts. Therefore, proper planning need to be carried out to avert such catastrophes, which include preparing adequate drainage, stormwater management and flood control projects. Sarawak, with its many and wide areas of catchments, is able to make use of rainfall through generation of hydroelectric power. The Upper Rajang catchment, being one of the largest river basins, has great potential in this respect. Usage of Department of Irrigation (DID) Sarawak supplied temporal profiles and IDF curves do not yield satisfying results when used in calculations in designing a Design Storm for large hydraulic structures, such as a barrage or a dam, therefore, a study was warranted in order to overcome this problem. The storm characteristics such as the temporal and spatial profiles are necessary in order to produce a Design Storm. This study utilizes a threshold in order to select a sufficient number of storms that is gathered from the historical data. The spatial profiles are generated from the daily rainfall records, whereas a temporal profile study was carried out using the hourly data, each collected from automatic and manual recording apparatus. A relationship between storm depth and area covered for high recorded storms was established. The study also points out differences observed between the temporal profiles available from historical data, and those provided by the DID guidelines.